Optimising human resource system strength in nurturing affective commitment: Do all meta‐features matter?. (11th September 2020) - Bos‐Nehles, Anna; Conway, Edel; Fox, Grace
Abstract: This study aims to examine three propositions of how human resource (HR) system strength meta‐features—distinctiveness, consistency and consensus—operate together to better understand how they relate to affective commitment. We test a continuum proposition based on an additive (the sum of all features) and a compensatory model (the features as counteractive), a precursor proposition based on a mediation model, and an equifinality proposition based on a configurational model (distinguishing between different profiles of the features). The findings, drawn from a survey of 2844 part‐time employees from a Dutch home care organisation, demonstrate that all three meta‐features are important for generating HR management system strength and affective commitment among employees, but not to the same extent. We also find evidence that consistency is positively and directly related, whereas distinctiveness and consensus are positively and indirectly related to affective commitment via consistency.